Heat transfer and strength analysis of column at extreme temperature - Abdul Ghani, Badri (Faculty of Mechanical Engineering, 1996)
Experimental and theoretical studies have been carried out to predict the fire resistance of protected I-shaped steel insulated with ceramic fibre. A mathematical model to calculate the temperature, deformations and fire resistance of the columns have been presented in this paper. The model enables the expansion of data on the protected steel columns involving ceramics which at present, consists predominantly with data for concrete columns.